Effects of hyperuricemia on renal function of renal transplant recipients: a systematic review and meta-analysis of cohort studies. - Yan Huang; Yu-Lin Li; He Huang; Ling Wang; Wen-Ming Yuan; Jing Li (PLoS ONE, 2012)
Background Hyperuricemia is an independent risk factor of nephropathy, but its role in renal transplant recipients (RTRs) is controversial. Methods Based on the methods of Cochrane systematic reviews, we searched MEDLINE (1948-2011.6), EMBASE (1956-2011.6), CBM (Chinese Biomedicine Database) (1978-2011.6) to identify cohort studies assessing the association between uric acid level and kidney allograft. Two authors independently screened the studies, assessed the risk of bias of included studies and extracted data. Unadjusted odds ratio (OR), mean difference (MD), adjusted hazard ratio (aHR) and their corresponding 95%CI were pooled to assess the effects of hyperuricemia on kidney allograft. Results Twelve cohort studies were included and the quality was moderate to high based on the NEWCASTLE-OTTAWA quality assessment scale. RTRs with hyperuricemia had lower eGFR (P<0.0001, 95%CI-16.34∼6.14) and higher SCr (P<0.00001, 95%CI 0.17∼0.31) than those with normal uric acid level. Meta-analysis showed that hyperuricemia was a risk factor of chronic allograft nephropathy (Unadjusted OR = 2.85, 95%CI 1.84∼4.38, adjusted HR = 1.65, 95%CI 1.02∼2.65) and graft loss (Unadjusted OR = 2.29, 95%CI 1.55∼3.39; adjusted HR = 2.01, 95%CI 1.39∼2.94). Conclusions Current evidence suggests that hyperuricemia may be an independent risk factor of allograft dysfunction. Hyperuricemia may modestly increase the risk of poor outcomes of RTRs. Future research is needed to verify whether lowering uric acid level could improve the kidney function and prognosis of RTRs with hyperuricemia.